Aprendizagem relacional, comportamento simbólico e ensino de leitura a pessoas com transtornos do espectro do autismo - Gomes, Camila Graciella Santos (2012)
The overall aim of this thesis was to investigate relevant variables to relational learning and the emergence of symbolic behavior in people with autism, in the teaching of reading. Were conducted three studies that are independent and yet complementary. Chapter 1 describes a study that evaluated the performance of forty participants with autism and forty with intellectual disabilities in identity matching-to-sample task, in the typical organization (one model and three comparisons) and in the organization with more than one model (three models and three comparisons), in two forms of presentation that needed different response modes: on tabletop and by computer. The general results of the participants indicated better performance in the organization with more than one model, in paper and in computer. Chapter 2 presents a study that aimed to teach basic reading skills to five participants with autism (four speakers and one nonspeaker), from the teaching of arbitrary relations among pictures and printed words, using adapted matching-to-sample task. Participants learned basic reading skills, but not showed combinatorial reading. Chapter 3 presents a study designed to teach combinatorial reading with comprehension for three participants with autism, from the teaching of naming syllables, words, pictures, and the formation of stimulus equivalence classes. Participants learned combinatorial reading with comprehension, with few training sessions and low numbers of errors during the teaching. The set of studies indicate the possibility of symbolic learning by people with autism since appropriate teaching procedures are used.